Impact of wrong-way risk on margin valuation adjustment - Binder, S (2021)
Valuation adjustments (XVA) have grown in popularity and importance since the Financial Crisis. In the post-Crisis environment, the value of a derivative can no longer be calculated simply as the risk-free price from by Black-Scholes theory, but other aspect, such as credit risk need to be accounted for as well. New regulations following the Crisis impose collateral requirements on over-the-counter derivatives, where initial and variation margin must be exchanged between trading counterparties. This introduces valuation adjustments that reflect the cost of funding for the derivative position. In particular, the Margin Valuation Adjustment (MVA) quantifies the cost of posting initial margin over the life of a trade.